Implementasi Metode Pendidikan Islam dalam Pembelajaran Kitab Kuning Di Pondok Pesantren NU Al Qomariah Galang - Khairani, Dede; Salminawati, Salminawati; Dahlan, Zaini (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Kitab kuning learning constitutes the core foundation of the scholarly tradition in Islamic boarding schools (pesantren). However, academic studies remain limited in explaining how classical Islamic pedagogy is adaptively implemented within contemporary educational contexts. This study addresses this gap by examining the actual practices of kitab kuning learning in a traditional pesantren. The study aims to analyze the planning and implementation of Islamic educational methods in kitab kuning instruction at NU Al-Qomariyah Islamic Boarding School, Galang. A descriptive qualitative approach with a case study design was employed. Data were collected through classroom observations, in-depth interviews with pesantren leaders, teachers, and students, and document analysis. The data were analyzed using the Miles and Huberman model, with trustworthiness ensured through triangulation and the criteria proposed by Lincoln and Guba. The findings indicate that kitab kuning learning is systematically planned based on students’ needs analysis, implemented through staged instructional methods (bandongan, sorogan, musyawarah, and bahtsul masāil), adapted to the epistemological characteristics of the texts, and reinforced through contextualized formal lesson planning (RPP). These findings demonstrate that pesantren pedagogy is adaptive, reflective, and oriented toward developing students’ competencies. This study contributes conceptually by showing that pesantren possess internal capacities to continuously reconstruct kitab kuning pedagogy without losing their scholarly identity.